Disease profile and outcomes of patients with candida auris infections, compared to other candida species, at a tertiary South African Hospital - Parak, Amirah (My University, 2020)
Introduction Multidrug resistant Candida auris is a novel and emerging threat worldwide. It has been identified in Africa, however, there is not enough data available comparing C. auris to other Candida species found in Africa. Objective To compare the clinical and laboratory features, risk factors, treatment and outcome of C. auris to the most virulent Candida species (Candida albicans) and a well-known azole resistant Candida species (Candida glabrata). Method Retrospective, cross-sectional, analysis of all patients with a positive culture for C. auris , from 1 January 2015 to 31 August 2018, at a tertiary South African Hospital. An equal number of patients with C. albicans and C. glabrata were matched for comparison. Results Forty-five cases of C. auris infection were identified. The median age was 32 years (IQR 26- 46) with 71.1% (n=32/45) being male. Median duration of hospital stay for C. auris was 64 days (IQR 39-88) and median time from admission to diagnosis was 35 days (IQR 21-53), both of which were significant compared to C. albicans and C. glabrata (p<0.001). Indwelling devices, previous antibiotic exposure and multiple surgical procedures were found to be significant risk factors. All C. auris isolates were healthcare associated with 80% (n=36/45) acquired in ICU. ICU admission was found to be a significant risk factor. There were no C. auris isolates resistant to amphotericin B or micafungin. Despite isolates having a low amphotericin B MIC, patients treated with amphotericin B alone, had a higher mortality (73.33%, n=11/15) than patients treated with an echinocandin (54.55%, n=6/11). The 30 day all-cause in-patient mortality was 42% (n=19/45) for C. auris, 36% (n=16/45) for C. albicans and 53% (n=24/45) for C. glabrata. Conclusion C. auris is an emerging multi drug resistant threat in South Africa. Improved access to echinocandins in the public sector is needed for the treatment of C. auris infections. In addition, implementation of improved infection prevention and control strategies are imperative to prevent this multi-drug resistant pathogen from becoming endemic in South Africa.
A research report submitted n fulfilment of the requirements for the degree of Master of Medicine to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, 2019